TINJAUAN ATAS PROSEDUR PEMBAYARAN SURAT PERTANGGUNGJAWABAN PADA PT ANGKASA PURA II (PERSERO) - Yuke Indah Selistia, (2020)
This Final Report is produced as a result of the Field Work Practices conducted at PT Angkasa Pura II (Persero) to review payment procedures at PT Angkasa Pura II (Persero). In general, payments have the same purpose as cash disbursements, namely to obtain optimal profits by facilitating the exchange of cash with suppliers to obtain the goods and services needed. The payment procedure discussed in this report is a payment procedure for Accountability Letter. Accountability Letter payment procedure starts from the creation of the payment voucher file and the Accountability Letter until it is paid to the recipient/staff on duty. Accountability Letter payments are usually paid with two payment methods, namely the cash and transfer methods. The Accountability Letter payment procedure certainly involves the parties related to the transaction so there is a need for an internal control system and supporting documents, such as the Accountability Letter, and a cost breakdown sheet. After doing the Job Training, the conclusion can be drawn will get experience directly involved in activities in the real world of work, and can add insight into the science of accounting and implement it.